Noncollinear parametric amplification in the near-infrared based on type-II phase matching. (September 2015) - Schmidt, C; Bühler, J; Heinrich, A-C; Leitenstorfer, A; Brida, D
Abstract Noncollinear parametric amplification based on type-II phase matching for the generation of ultrabroadband and tunable spectra in the near infrared is investigated. In a noncollinear geometry the group velocity matching condition between signal and idler can be obtained in frequently used crystals such as β-barium borate (BBO) even for wavelengths fully located in the anomalous dispersion region. The extremely broadband operation, peculiar tuning possibilities and straightforward experimental implementation with the standard BBO crystal pave the way for a versatile NIR source in ultrafast spectroscopy.